The history and philosophy of materialism - Wolfe, Charles T. (Routledge, Taylor & Francis Group, 2025)
"Materialism - the view that facts are dependent upon or reducible to physical processes - is one of the most long-standing and controversial of all philosophical theories. Originating in the ancient world, its proponents include Epicurus, Hobbes, Hume, Darwin and Marx, whilst its impact on twentieth-century physics and the nature of consciousness reverberates strongly today. It is also an important yet generally overlooked feature of Indian, Chinese and Islamic thought. This major collection, the first of its kind, explores the fascinating philosophical history of materialism, from the ancient world to the twentieth century. Comprising thirty-one chapters by an international team of contributors, the volume is divided into six clear parts: Ancient, Non-Western and Medieval Philosophy Renaissance and Early Modern Philosophy Enlightenment Materialisms Nineteenth-Century Philosophy Twentieth-Century Philosophy Contemporary Philosophy: Philosophy of Mind, Metaphysics and Critique. Within these sections key topics are covered, including materialism in classical Greek thought; materialism in Indian and Chinese thought; Renaissance materialism and anti-materialism; materialism and Islamic philosophy; materialism in the French and German Enlightenment; atheism and materialism; the nineteenth-century materialist controversy; materialism and debates in physics; Marxism and materialism; physicalism; and the new materialism. The History and Philosophy of Materialism is ideal for those studying and researching the history of this vital philosophical movement, especially those with an interest in the history and philosophy of science, ancient and early modern philosophy and the Enlightenment. It will also be valuable reading for those in related disciplines such as History, Sociology and Religion."
Keywords: Ideengeschichte; Materialismus; Materialism / Philosophy; Materialism / History; Aufsatzsammlung